Development of Globalization Process and the WTO Activity - Dolgov, Sergej Ivanovich (Российский внешнеэкономический вестник, 2024)
In the article modern globalization processes in economy and international trade, their influence on WTO activities, and the agenda of multilateral trade negotiations are considered. Special attention is paid to the change in the balance of power in the world economy and trade, development of international supply chains and participation of developing countries in them, as well as to topical subjects of multilateral trade negotiations and the expected agenda of the 9th WTO Ministerial conference in Bali.